Analyzing the effects of orientation, window size and position on solar heat gain for four Indian cities - Kaushik S, Amalan Sigmund; Amraotkar, Sheetal (Science, Engineering and Health Studies, 2026)
The orientation of a building is the most important passive design strategy to achieve an energy-efficient design. Solar insolation studies help identify orientations that minimize solar heat gain. However, existing literature often overlooks the challenges posed by site constraints that prevent implementing the optimal orientation. India, covering just 2.4% of the world’s land area but accommodating 18% of the global population, faces a significant land scarcity issue. Consequently, the available development sites may not allow for the ideal orientation. In this research, in order to address this issue, Trichy, Chennai, and Mumbai, Kolkata across India were chosen and a solar insolation study was conducted for four different possible orientations of buildings in each of the cities and the best orientations were identified. Subsequently, the empirical calculation method outlined in GRIHA was used to calculate the ideal window design (size and position) for all orientations. The findings reveal that a north–south–oriented building module (M1) minimizes solar heat gain in Trichy, Chennai, and Mumbai, while a northeast–southwest orientation (M4) is optimal for Kolkata; moreover, orientation-responsive window redistribution reduces annual solar heat gain by up to 11.55% even in non-optimal orientations. The findings provide a transferable reference framework for designers to apply the methodology across other cities.